Repositioning but where – Is the UNDS fit for middle-income countries? - Nils-Sjard Schulz (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
After intense negotiations, the United Nations General Assembly has endorsed the reform of the United Nations Development System (UNDS). Most players in New York, including Secretary-General António Guterres and ambassadors to the United Nations, are optimistic that the UNDS will now take the multi-adjective route requested by the General Assembly (“more strategic, accountable, effective, transparent, collaborative, efficient, effective and result-oriented”). However, the reform's actual litmus test will take place at the country level. Governments are expecting the UNDS to support the domestic implementation of the 2030 Agenda for Sustainable Development. The ever-expanding and diverse family of middle-income countries (MICs), in particular are demanding increased and better engagement with the UN agencies, commissions, funds and programmes working on sustainable development challenges and opportunities. Indeed, the 2030 Agenda and the UN's role in the agreement's success are to a large degree dependent on progress in both lower and upper MICs. All essential elements of the 2030 Agenda are under stress in MICs: The MICs economies are transitioning from survival to prosperity; their societies are facing stark inequality and accelerated modernisation, and their ecosystems are under extreme demographic and economic pressure. MICs also are struggling with increasingly urgent cross-sector challenges, such as climate resilience, migration, security and rule of law. Despite the relevance and specific demands of MICs, the UNDS remains largely incapable of catering to their priorities at strategic and operational levels. The UNDS is not the only development actor that supports MICs in their efforts, but it needs to become a valuable partner for governments, especially in advising and supporting government-led implementation of the 2030 Agenda. To seize the momentum of global development, the ongoing reform must make the system “fit for MICs,” starting with the following fields of action: 1. Fully align with MICs priorities: the UNDS needs to be up to speed with country initiatives in terms of governance, planning, statistics and partnerships. 2. Provide relevant high-quality support: Beyond the poverty lens, UNDS should increase its capacities to deliver support that is relevant to complex national priorities of MICS. 3. Make financing a top priority: the UNDS has a key role to play in supporting MICs exposed to manifold financing challenges, from decreasing Official Develop¬ment Assistance (ODA) to unsustainable debt.
Keywords: 330; Agenda 2030; Deutsche + Europäische + multilaterale Entwicklungspolitik